Strategi Komunikasi Politik PDI-P Menjelang Pemilu 2024 di Masa Pandemi COVID-19: Refleksi Partisipasi Politik Masyarakat di Era Modern Dalam Mewujudkan Demokrasi - Alfan Bachtiar (Brand Communication, 2022)
The 2024 elections have raised public concern due to the covid- 19 pandemic which threatens the safety of many people if the people do not participate in realizing democratic elections. Political parties as the most essential organs in building public opinion are needed to realize this participation. The development of information technology creates a new form of political participation based on online media. At present, it can be seen that the Indonesian Democratic Party of Struggle (PDI-P) has massively installed Puan Maharani’s billboards titled “Wings of Diversity” massively throughout Indonesia. Therefore, this study analyzes how the development of Information and Communication Technology (ICT) can affect the form of public political participation and how PDI-P adjusts. This research uses Aeron Davi’s Theory about the importand role of online media as a forum for alternative political participation of the community in realizing democracy in modern times where informations technology offers tools to apply democratic theory, especially regarding more inclusive public participation between ordinary citizins and political elites. The results of the analysis show that PDI-P is aware of the large potential for societal divisions in the 2024 Election so that the direction of its political communications is not only oriented toward winning the election but also encouraging community unity in democratic political participation but still not optimally utilizing online communications channel. PDI-P prioritizes traditional poltical communication. Several improvements need to be made to minimize the negative impact of political participation through digital online media.